Seismic Fragility Assessment for Buildings due to Earthquake Excitation - NAZRI, FADZLI MOHAMED (SpringerBriefs in Computational Mechanics,, 2018)
This book presents a simplified approach to earthquake engineering by developing the fragility curve for regular and irregular moment-resisting frames based on different types of structural material, height, and ground motion records. It examines six sets of concrete and steel frames, which vary in terms of their height (3-, 6- and 9-storey) and include regular and irregular frames. Each structure frame was designed based on Eurocode 2 and 3 with the aid of Eurocode 8 for earthquake loading. The SAP2000 software was used as the main tool for the pushover analysis and incremental dynamic analysis. Readers are first provided with background information on the development of nonlinear analysis in earthquake engineering. Subsequently, each chapter begins with a detailed explanation of the collapse of the structures and the application in nonlinear analysis. As such, the book will greatly benefit students from both public and private institutions of higher, particularly those who are dealing with the subject of earthquake engineering for the first time. It also offers a valuable guide for Civil Engineering practitioners and researchers who have an interest in structural and earthquake engineering.